Devising an impactful religious moderation workshop for teachers and principals: The practice of Ice Berg analysis and U theory perspective - Yusuf Hanafi; Muhammad Saefi; M. Alifudin Ikhsan; Tsania Nur Diyana; Faris Khoirul Anam; Oktaviani Adhi Suciptaningsih (Journal of Community Service and Empowerment, 2024)
In the academic setting, teachers and school principals are often faced with the problem of identifying and developing strategies to strengthen the atmosphere of religious moderation. Unfortunately, resources for training and support are scarce. Our study presents the design and assessment of a religious moderation workshop utilizing the problem-based discussion method, supported by Ice Berg and U theory perspective analysis. This two-session workshop aims to bolster religious moderation among school personnel. During the initial session, attendees were presented with strategies to empower religious moderation and state defense. In the subsequent meeting, attendees were encouraged to engage in problem-solving exercises focused on acts and behaviors of intolerance. Not to mention, the educators and administrators have acquired content and pedagogical expertise regarding religious moderation and state defense, which can be applied in classroom and school settings. Additionally, participants expressed a positive belief that the training effectively exemplified the integration of character-building subject matter, religious moderation, state defense, and instructional strategies. As a result, the workshop for teachers and school principals was deemed successful and effective.